The impact of a flipped classroom design on learning performance in higher education: Looking for the best "blend" of lectures and guiding questions with feedback. (April 2017) - Thai, Ngoc Thuy Thi; De Wever, Bram; Valcke, Martin
Abstract: The present study examines the differential impact of studying in a Flipped Classroom (FC) setting, as compared to a Blended Learning (BL), a Traditional Learning (TL), and an E-Learning (EL) setting on learning performance, self-efficacy beliefs, intrinsic motivation, and perceived flexibility. Participants were second year undergraduate students ( N  = 90), enrolled in the "Invertebrates" course in Can Tho University (Vietnam). Participants were randomly assigned to one of the four experimental conditions (TL n  = 22, BL n  = 22, FC n  = 23, EL n  = 23). Two instructional elements - (1) lectures and (2) guiding questions - were presented through two different modes (online and face-to-face). In the blended conditions (BL and FC) the mode of these elements were altered. The results show that learning performance was superior in the FC setting as compared to other learning settings TL ( Cohens' d  = 1.58), EL ( Cohens' d  = 1.01) and BL ( Cohens' d  = 0.71). Students in the BL setting had a higher learning performance as compared to the EL setting. In addition, we observed that studying in a FC setting had a positive effect on self-efficacy beliefs and intrinsic motivation, but not on perceived flexibility. These findings suggest that the FC setting could be a promising way of enhancing students' learning performance. Highlights: A flipped classroom results in higher learning performance compared to Face-to-Face and Fully E-Learning. A blended learning design results in higher learning outcomes compared to Fully E-Learning. Blended learning has significant effect on self-efficacy and intrinsic motivation as compared to Fully E-Learning.